1976
DOI: 10.1103/physrevlett.36.1028
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanism for the Formation of Yrast Traps at Very High Spins

Abstract: We discuss a possible mechanism, namely the maximization of the overlap of nucleonic wave functions by alignment, for the formation of isomers in the yrast band in the rare nuclei at very high spin states 0 Our results indicate that the possibility of existence of such yrast traps is restricted to a few nuclei with special irregularities in the singleparticle level s e With the advent of heavy-ion accelerators it has been made possible to transfer in a fusion experiment angular momenta as large 1 as ~ 60/z in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…2.2, the basic case of two identical particles in a single-j shell interacting through a short-range attractive interaction, such as a δ force or a quadrupole-quadrupole force [146], leads naturally to isomers. The 0 + state in which the particle angular momenta are anti-aligned (or more generally, paired) is depressed in energy, and a gradual bunching of levels up to the maximum spin of 2j −1 occurs.…”
Section: Residual Interactions and The Empirical Shell Model (Esm)mentioning
confidence: 99%
See 1 more Smart Citation
“…2.2, the basic case of two identical particles in a single-j shell interacting through a short-range attractive interaction, such as a δ force or a quadrupole-quadrupole force [146], leads naturally to isomers. The 0 + state in which the particle angular momenta are anti-aligned (or more generally, paired) is depressed in energy, and a gradual bunching of levels up to the maximum spin of 2j −1 occurs.…”
Section: Residual Interactions and The Empirical Shell Model (Esm)mentioning
confidence: 99%
“…High-spin isomers are known to dominate the yrast structure of many nuclei in the region near 146 Gd, where spherical shape is stabilised by the N = 82 shell gap combined with the Z = 64 sub-shell closure. The properties of nuclei in this region were reviewed by de Voigt et al [36], but since then many new isomers have been observed in nuclei near N=81-85 and Z=60-71, in parallel with studies in the radon region.…”
Section: Nuclei Near 146 Gdmentioning
confidence: 99%
“…In general, one can therefore conclude that at the end of the shell the nucleus prefers to rotate around the prolate symmetry axis and at the beginning around an oblate symmetry axis at high spin states. Both results are due to the MONA effect [12]: The increased overlap near the equator due to alignment of the single particle (or hole) angular momenta produces for particles (beginning of shell) a rotation around an oblate symmetry axis while the same effect for holes (at the end of a shell) yields a rotation around a prolate symmetry axis.…”
Section: Ej(fl Y Ana~)-(~ Y Anap I/~l ~ Y Zl~ap> + Ec(~ Y)mentioning
confidence: 86%
“…The stabilisation of the rotation around the prolate symmetry axis at the end of the rare earth region up to 2~ seems to be mainly due to the MONA effect [12]: The high angular momentum is formed by alignment of the single hole angular momenta along the rotational axis. Since the holes are concentrated near the equator this favours rotation around a prolate symmetry axis at the end of a shell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation